2018
DOI: 10.1097/md.0000000000012908
|View full text |Cite
|
Sign up to set email alerts
|

Anthracycline versus nonanthracycline adjuvant therapy for early breast cancer

Abstract: Purpose:The clinical benefits provided by using anthracycline-contained regimens in patients with early breast cancer (EBC) remain uncertain. This meta-analysis used data from all relevant trials to compare treatment outcomes for patients with EBC receiving adjuvant chemotherapy with non–anthracycline-contained regimens or anthracycline-contained regimens.Patients and Methods:Individual patient data were collected on 7 randomized trials comparing non–anthracycline-contained regimens with anthracycline-containe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 33 publications
3
16
0
Order By: Relevance
“…[3] In the TRAIN 2 study, there was no signi cant difference between the regimen containing anthracyclines and the regimen that did not, and it was reported that it was preferable not to use anthracyclines. [13] The pathological complete response rates obtained in our study was found to be similar in anthracycline containing and not containing regimen groups. All patients with cardiotoxicity (5.8%) were patients who had received the treatment regimen containing anthracycline.…”
Section: Discussionsupporting
confidence: 73%
“…[3] In the TRAIN 2 study, there was no signi cant difference between the regimen containing anthracyclines and the regimen that did not, and it was reported that it was preferable not to use anthracyclines. [13] The pathological complete response rates obtained in our study was found to be similar in anthracycline containing and not containing regimen groups. All patients with cardiotoxicity (5.8%) were patients who had received the treatment regimen containing anthracycline.…”
Section: Discussionsupporting
confidence: 73%
“…And during these cycles, all of our study participants received only Adriamycin and cyclophosphamide from both regimens. Recent systematic review and meta-analysis indicated that both hematological (i.e., neutropenia and others) and nonhematological toxicities (i.e., nausea, vomiting, and mucositis) were common in anthracycline (Adriamycin) containing regimen for breast cancer [20]. e epithelium covering the entire gastrointestinal tract (GIT) is rapidly dividing, and thus it is highly susceptible to chemotherapy which leads to probably the most feared adverse effects, nausea and vomiting [21].…”
Section: Discussionmentioning
confidence: 99%
“…In the adjuvant setting, anthracycline-containing regimens have been reported to be superior to non-anthracycline-containing regimens for both DFS and OS in patients with early breast cancer. 33 As NAC, anthracycline-containing regimens are reported to be associated with higher pCR rates but without statistical significance compared to non-anthracycline-containing regimens in patients with TNBC. 19 Although TNBC has been reported to be more sensitive to anthracycline-containing regimens than non-TNBC, 34 the real benefit of adding anthracycline to the NAT regimen in patients with TNBC has been controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Anthracyclines have been commonly used as a component in adjuvant or neo‐adjuvant therapy of breast cancer. In the adjuvant setting, anthracycline‐containing regimens have been reported to be superior to non–anthracycline‐containing regimens for both DFS and OS in patients with early breast cancer 33 . As NAC, anthracycline‐containing regimens are reported to be associated with higher pCR rates but without statistical significance compared to non–anthracycline‐containing regimens in patients with TNBC 19 .…”
Section: Discussionmentioning
confidence: 99%